Pengaruh Implementasi TQM Terhadap Penurunan Tingkat Cacat Produk Di PT. Ciptaunggul Karya Abadi - Nadiahun Nasywa; Apid Hapid Maksum; Wahyudin; Billy Nugraha; Seka Pertiwi (UNISTEK, 2026)
Ciptaunggul Karya Abadi is a private company engaged in the Manufacturing of Metal Stamping Parts, Tools and Dies. In the face of fierce industry competition, the consistency of product quality is a determining factor for competitiveness. The high rate of product defects is a major concern for companies as it impacts cost, efficiency, and customer satisfaction. This study aims to analyze the effect of the implementation of Total Quality Management (TQM) on reducing the level of product defects. The method used was a case study with data collection through direct observation, interviews with stakeholders, and document analysis over a period of four months. The results show that the application of TQM elements such as customer focus, obsession with quality, scientific approach, long-term commitment, teamwork, continuous system improvement, education and training, controlled freedom, unity of purpose, and employee involvement and empowerment have a significant effect in reducing product defects. The implementation of TQM is also able to create a better quality culture in the production environment. Based on the results of the analysis, it can be concluded that PT. Ciptaunggul Karya Abadi has implemented all elements of Total Quality Management (TQM) as an effort to improve product quality and reduce the level of defects, but the implementation is not fully optimal. Therefore, it can also be concluded that Total Quality Management (TQM) is an effective strategic approach to improve product quality in a sustainable manner.